Effect of Fatty Acids on Production and Immunological Status of Vaccinated Broiler Chickens - Bapeer, Yunis A.; Shamaun, Alaa A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2015)
This study was conducted on 400 one day-old male broiler chicks (Ross-308) randomly divided to 2 main groups, 1st main group (GA) feeding basal diet with medium chain fatty acid (MCFA) at rate of 0.15% and divided to four subgroups, 3 subgroups vaccinated with different routes with Newcastle Disease (ND) and non-vaccinated group. The 2nd main group (GB) feeding basal diet without MCFA and divided as the same 1st main gruop. The parameters used in this study included: body weight (BW), phagocytic index (PI), stress index (SI) and weight of spleen and bursa of Fabricious. The aim of this study to evaluate the effect of (MCFA) on these parameters. The experiment lasted for 42 days. Results indicated that additional dietary fatty acid (FA) significantly increased average body weight during the different weeks of the experiment over the basal diet group of birds. Data of PI revealed that birds fed FA supplemented diet had lower values of PI than the basal diet on 2W and the reverse was true on 4W of the experiment. The non-vaccinated birds, on the other hand, showed lowest PI values on 2W and 4W of age. As for, SI a pronounced difference was found due to the two types of diet, and the vaccination methods, as well.